Examination of historical textiles with dyestuff analyses by TLC and derivative spectrophotometry - (:unkn) unknown (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 1997)
A group of historical textiles in the Topkapi Museum, i.e., silk brocades classified as 16th century pieces by art historians, were investigated by TLC and spectrophometric analyses of their dyestuffs for the purpose of dating these pieces. The dyestuffs contained intextile fibers were extracted with acid solutions of varying strength, and the acid extracts were analyzed by both TLC and spectrophotometry, either directly or after an organic solvent extraction step. The first derivative spectra proved to provide more information than the main spectra. In order to eliminate possible interferences in spectrophotometry arising from impurities in the fibers, e.g., compounds containing amino-and carboxyl-groups or mordent metals, the uncoloured fibers which had been prepared for dyeing were subjected to the same type of extraction, and the aqueous of organic extracts obtained were used as a reference. Thus, first derivative spectrophotometry with the developed reference and blank emerges as a new tool for analyzing the extracts of historical textiles as an indispensable aid to dating efforts.